The conceptualization and management of quality time in young dating couples in Metro Manila - La'O, Paolo Noel Coronel; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
The objective of this study is to investigate the conceptualization and management of quality time as defined by young dating couples, as well as the individual contexts that influence both. Due to the COVID-19 pandemic, only 4 responding couples could be interviewed, for a total of 8 individual interviews. Each interview was analyzed for consistency, commonalities in the given definitions of the concept, as well as in the respondent’s answers to the questions regarding the formation of the concept. Findings show that the concept of quality time for all individuals is flexible in terms of the necessary elements to enjoy such, but firm in it’s perceived purpose, following an inferential concept model. In terms of management, it was found that both how one manages said time and the activities that fall under the concept will adjust according to what the subject is willing to adjust, to the point of expanding. one’s definition of quality time, and dropping certain aspects, such as the necessity for physical presence. Such flexibility was used to adapt to shifts in relationship dynamics, such as increased distance. It was also found that most subjects had difficulty identifying influences on their individual concepts of quality time, aside from personal experience. It should be noted that common preexisting definitions may have some influence over respondents perceptions, as most respondents initially listed activities mostly consistent with common preexisting definitions of quality time, departing from such only upon further inquiry. Recommendations to expand the study through sheer number of respondents in order to test initial findings were given, as well as individual case studies to explore potential tertiary influences, and longitudinal studies to observe the development of the concept over time.
Thesis (Bachelor of Science in Home Economics) -- University of the Philippines Diliman
Bibliography: pages 47-48.
Keywords: COVID-19 pandemic, 2020 - -- Philippines -- Metro Manila; Dating (Social customs) -- Philippines -- Metro Manila; Minority couples -- Philippines -- Metro Manila; Time management -- Philippines -- Metro Manila